The latissimus dorsi‐groin‐lymph node compound flap: A comprehensive technique with three features including skin coverage, restoration of motor function, and prevention of upper limb lymphedema. Issue 8 (14th October 2015) - Nicoli, Fabio; Orfaniotis, Georgios; Lazzeri, Davide; Lim, Seong Yoon; Kiranantawat, Kidakorn; Chen, Pei‐Yu; Ciudad, Pedro; Chilgar, Ram M.; Sapountzis, Stamatis; Sacak, Bulent; Chen, Hung‐Chi
Abstract : Reconstruction of complex upper extremity defects requires a need for multiple tissue components. The supercharged latissimus dorsi (LD)‐groin compound flap is an option that can provide a large skin paddle with simultaneous functional muscle transfer. It is necessary to supercharge the flap with the superficial circumflex iliac pedicle to ensure the viability of its groin extension. In this report, we present a case of a supercharged LD‐groin flap in combination with vascularized inguinal lymph nodes, which was used for upper limb reconstruction in a young male patient, following excision of high‐grade liposarcoma. Resection resulted in a 28 cm × 15 cm skin defect extending from the upper arm to the proximal forearm, also involving the triceps muscle, a segment of the ulnar nerve and the axillary lymph nodes. Restoration of triceps function was achieved with transfer of the innervated LD muscle. Part of the ulnar nerve was resected and repaired with sural nerve grafts. Post‐operatively, the flap survived fully with no partial necrosis, and no complications at both the recipient and donor sites. At 1‐year follow up, the patient had a well‐healed wound with good elbow extension (against resistance), no tumor recurrence, and no signs of lymphedema. We believe this comprehensive approach may represent a valuable technique, for not only the oncological reconstruction of upper extremity, but also for the prevention of lymphedema. © 2015 Wiley Periodicals, Inc. Microsurgery 36:689–694, 2016.